(untitled) (European Journal of Health Research, 2018)
Cognitive impairment and dementia are disorders characterized by decreased cognition that affects one or more aspects of it, coming to interfere with activities of daily living of the person. Epidemiological studies have shown strong evidence of association between oral health status and cognitive impairment/dementia. The aim of this study was to determinate the impact of cognitive impairment on oral health of a eldery population. It has been conducted a study based on secondary data of Periodontitis-Dementia study, a case-control study conducted in Granada with 564 patients over 65 years. Cases were older people diagnosed with cognitive impairment or dementia and controls were healthy subjects without cognitive impairment. Data collected were: oral hygiene, teeth present, DMFT, plaque index, bleeding index, probing depth and clinical attachment loss. A statistically significant association was observed between level of cognitive impairment and oral health status, finding a higher level of plaque and bleeding indexes and an association between the extent of periodontal disease and severity of cognitive impairment, after controlling for confounding variables such age, sex, educational level, tobacco or alcohol. There is a statistically significant association between level of cognitive impairment and periodontal health status.